Novel evidence that nitric oxide of the medial septal area influences the salivary secretion induced by pilocarpine - Saad, W. A.; Guarda, IFMS; Camargo, LAD; dos Santos, TAFB; Simoes, S.; Guarda, R. S. (Elsevier B.V., 2002)
Our studies have focused on the effect of injection of L-NAME and sodium nitroprussiate (SNP) on the salivary secretion, arterial blood pressure, sodium excretion and urinary volume induced by pilocarpine which was injected into the medial septal area (MSA). Rats were anesthetized with urethane (1.25 g/kg b. wt.) and a stainless steel cannula was implanted into their MSA. The amount of saliva secretion was studied over a five-minute period after injection of pilocarpine into MSA. Injection of pilocarpine (10, 20, 40, 80, 160 mug/mul) into MSA produced a dose-dependent increase in salivary secretion. L-NG-nitro arginine methyl-esther (L-NAME) (40 mug/mul), a nitric oxide (NO) synthase inhibitor, was injected into MSA prior to the injection of pilocarpine into MSA, producing an increase in salivary secretion due to the effect of pilocarpine. Sodium nitroprussiate (SNP) (30 mug/mul) was injected into MSA prior to the injection of pilocarpine into MSA attenuating the increase in salivary secretion induced by pilocarpine. Medial arterial pressure (MAP) increase after injections of pilocarpine into the MSA. L-NAME injected into the MSA prior to injection of pilocarpine into MSA increased the MAP. SNP injected into the MSA prior to pilocarpine attenuated the effect of pilocarpine on MAP. Pilocarpine (40 mug/mul) injected into the MAS induced an increase in sodium and urinary excretion. L-NAME injected prior to pilocarpine into the MSA increased the urinary sodium excretion and urinary volume induced by pilocarpine. SNP injected prior to pilocarpine into the MSA decreased the sodium excretion and urinary volume induced by pilocarpine. All these roles of pilocarpine depend on the release of nitric oxide into the MSA. We may also conclude that the MSA is involved with the cholinergic excitatory mechanism that induce salivary secretion, increase in MAP and increase in sodium excretion and urinary volume. (C) 2002 Elsevier B.V. All rights reserved.
Keywords: pilocarpine; nitric oxide; septal area; salivation; arterial pressure; sodium excretion